PENGARUH METODE PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR PAI KELAS V SEKOLAH DASAR - Irja Putra Pratama; Muslih Hidayat; Aristophan Firdaus; Eko Purnomo (Raudhah - Proud To Be Professional, 2023)
This study aims to determine the effect of using the talking stick learning method on student learning outcomes in PAI subjects. The research is a quantitative pre-experimental design. The design used is a type of One-group pretest-posttest design. The sample in this article was 22 fifth-grade students of SD Negeri 04 Tanjung Batu Ogan Ilir. The data collection technique used a multiple choice test of 20 pretest and posttest questions. Data information is processed using SPSS 23 data analysis techniques using the results of the t-test. The results of the study can be obtained and proven by calculating the pretest value received at 71.6364 and the posttest value with the average value of 85.5455. The normality test formula shows that the significance obtained by the pretest data is 0.292>0.05, and the importance obtained by the posttest information is 0.012>0.05, meaning that the pretest-posttest data of class V students are normally distributed. The results of data analysis show that the data obtained influence student learning outcomes before and after the application of existing methods in class V, getting significant results from existing tests, namely 0.000 <0.05, which means Ho is rejected while Ha is accepted.